Dynamics of Adaptive Drive Equipment for Forming Billets Bricks - Purdyk, Victor; Brytskiy, Oleksandr; Sapognik, Vitaliy (International Journal of Engineering and Technology, 2018)
Abstract. In this paper, an option is provided for upgrading equipment for the formation of raw bricks by creating a compact design with an adaptive drive based on hydroautomatics. The basis of modernized construction is the further scheme of formation of executive bodies on the movement of workpieces. A mathematical model of equipment was developed that takes into account the peculiarities of the formation of forces of friction that arise during the movement in the executive power bodies and their inertia. As a result of the study of a mathematical model in the Matlab Simulink environment, the influence on the dynamics of motion of the main executive bodies of some parameters of the drive system is determined. It is noted that the dynamics of the drive is most affected by such parameters as the weight of moving executive bodies, the friction force is given, the hydraulic stiffness of the pressure line of the pumping station is given. The method of calculating the power of the pumping station of the adaptive drive was proposed, on the basis of which the design documentation was developed and the prototype of the equipment was manufactured.Â Â